Characteristics, Emission Sources, and Risk Factors of Heavy Metals in PM2.5 from Southern Malaysia - Alias, Nor Fathiah (Amer Chemical SOC, 2020)
Exposure to fine particulate-bound toxic metals in ambient air poses adverse effects to human. This study aims to determine the spatial variability in heavy metals in PM2.5, samples, for identifying their potential sources and to perform health risk modelling. PM2.5 samples were collected using a high-volume sampler on a 24 h basis from three sites in Johor areas in Malaysia from January to March 2019. Metals were initially extracted using microwave-assisted digestion and the metal concentrations were analyzed using inductively coupled plasma mass spectroscopy. Overall, the abundant metals in PM2.5 among the metals analyzed were Zn with mean 29.92 ng/m(3 )and Se with mean 27.02 ng/m(3). The sources of PM-bound metals were identified using absolute principal component score with multiple linear regression. The major contribution was noted from vehicle emission (41%). Other potential sources for the metals in PM2.5 were from coal-fired power plants (34%) and oil refineries and industrial emission (4%), leaving 22% of metals undefined. From the health risk analysis, the hazard quotient (HQ) and excess lifetime cancer risk (ELCR) values of the metals were within the tolerance level. The trend for HQ values was Co < Zn < Pb < Cu < Ni < As for adolescents and Co < Zn < Cu < Pb < Ni < As for adult age, whereas for ELCR values, the trends were the same for both adolescent and adult age groups as Pb < Ni < As. Few of the toxic metals showed comparatively high HQ values that might be a risk in long-term exposure. Considering the highest noted contribution from vehicular emissions, it is advised to raise public awareness to practice carpooling and use public transportation to reduce emissions from vehicular sources.